Structural and catalytic characterization of a thermally stable and acid‐stable variant of human carbonic anhydrase II containing an engineered disulfide bond. (30th July 2013) - Boone, Christopher D.; Habibzadegan, Andrew; Tu, Chingkuang; Silverman, David N.; McKenna, Robert
Abstract : The carbonic anhydrases (CAs) are a family of mostly zinc metalloenzymes that catalyze the reversible hydration of CO2 to bicarbonate and a proton. Recently, there has been industrial interest in utilizing CAs as biocatalysts for carbon sequestration and biofuel production. The conditions used in these processes, however, result in high temperatures and acidic pH. This unfavorable environment results in rapid destabilization and loss of catalytic activity in CAs, ultimately resulting in cost‐inefficient high‐maintenance operation of the system. In order to negate these detrimental industrial conditions, cysteines at residues 23 (Ala23Cys) and 203 (Leu203Cys) were engineered into a wild‐type variant of human CA II (HCAII) containing the mutation Cys206Ser. The X‐ray crystallographic structure of the disulfide‐containing HCAII (dsHCAII) was solved to 1.77 Å resolution and revealed that successful oxidation of the cysteine bond was achieved while also retaining desirable active‐site geometry. Kinetic studies utilizing the measurement of 18 O‐labeled CO2 by mass spectrometry revealed that dsHCAII retained high catalytic efficiency, and differential scanning calorimetry showed acid stability and thermal stability that was enhanced by up to 14 K compared with native HCAII. Together, these studies have shown that dsHCAII has properties that could be used in an industrial setting to help to lower costs and improve the overall reaction efficiency.